Infertility Stigma and Domestic Violence: A Cross-Sectional Study - Maryam Soruri Zad; Mahboube Taebi (Iranian Journal of Nursing and Midwifery Research)
Background: Infertility stigma is one of the well-known psychosocial problems and can disrupt the mental health of infertile women and their family relationships. This study evaluated the relation between infertility stigma and domestic violence in infertile women. Material and Methods: This was a cross-sectional study that was conducted on 300 women who referred to the Fertility and Infertility Center of Isfahan, IRAN (2022–2023) using a convenient sampling method. Data gathering tools were WHO Standard Domestic Violence questionnaire and Female Infertility Stigma Instrument (ISI-F). Data were analyzed using SPSS software version 16 (Pearson correlation, Mann–Whitney, Kruskal–Wallis, and multivariate linear regression analysis). This article has been edited based on the STROBE checklist. Results: The mean (SD) score of infertility stigma was 64.79 (14.70) (out of 100). The mean (SD) score of domestic violence was 10.94 (16.61) (out of 100). There was a significant positive relation between the score of infertility stigma and the total score of domestic violence, physical violence, mental violence, and sexual violence p<0.001. The highest correlation was found between mental violence and infertility stigma (r = 0.359). Economic status (p = 0.001), infertility factor (p = 0.007), and infertility stigma p<0.001 were predictors of domestic violence. Conclusions: Infertility stigma was related with all the aspects of domestic violence. Infertility stigma was a predictor of domestic violence. It is necessary to plan interventions to deal with infertility stigma and domestic violence in infertile women. Psychological counseling should be considered along with infertility treatment.